Impact of hormonal contraception on female sexual function among university students of reproductive age in the Dominican Republic: A cross-sectional study - Sabrina Verdeja-Vicente; Amanda R Villalona-Lluveres; Jenny L Cepeda-Marte (Instituto Tecnológico de Santo Domingo (INTEC), 2023)
Objective. Identify if hormonal contraception (HC) has a negative impact on female sexual function (FSF) in a group of university students of reproductive age in the Dominican Republic. Methods: A total of 251 female students between ages 18-30 completed an online survey to evaluate their FSF with the Female Sexual Function Index (FSFI), as well as their relationship with their contraceptive method (CM). Results were analyzed using descriptive statistics and standard non-parametric tests.  Results: The groups in this study were: never used HC (NHC) n=80 (31.9%), uses HC (UHC) n=132 (52.6%), and abandoned HC (AHC) n=39 (15.5%). The mean grade for the FSFI for all groups was 28.84 (2.0-36.0). UHC was the lowest grade (28.15) when compared to NHC (29.84) and AHC (29.23) (p=0.023). UHC had the most participants at risk of female sexual dysfunction (FSD). The highest level of general satisfaction with their CM was in the UHC group (90.2% reported to be satisfied/very satisfied).  Conclusion: There is a weak correlation between HC use and the increased risk of FSD with statistical significance (Rho=0.132; p=0.037). FSF levels in UHC were lower than in the NHC group. Despite having the greatest level of satisfaction with their CM, UHC reported the highest level of FSF disturbance. The disturbance of FSF due to HC use was a strong predictor of abandonment (65%).